2014
DOI: 10.1136/bmjopen-2014-005240
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospital accreditation on clinical documentation compliance: a life cycle explanation using interrupted time series analysis

Abstract: ObjectiveTo evaluate whether accredited hospitals maintain quality and patient safety standards over the accreditation cycle by testing a life cycle explanation of accreditation on quality measures. Four distinct phases of the accreditation life cycle were defined based on the Joint Commission International process. Predictions concerning the time series trend of compliance during each phase were specified and tested.DesignInterrupted time series (ITS) regression analysis of 23 quality and accreditation compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 20 publications
3
72
1
Order By: Relevance
“…This reaction by the hospitals takes place after the on-site survey, seemingly because of the lack of a comprehensive unannounced visit programme by the surveyors (Aryankhesal and Sheldon 2010). This point is supported by Devkaran and O'Farrell (2014), who reported that mandatory accreditation shifts the goal to survey compliance instead of quality improvement, does not embed the standards into practice and does not sustain performance. Another reason to reject the requirements may be because of power dynamics, as the results suggest that native Saudis were less motivated to change.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction by the hospitals takes place after the on-site survey, seemingly because of the lack of a comprehensive unannounced visit programme by the surveyors (Aryankhesal and Sheldon 2010). This point is supported by Devkaran and O'Farrell (2014), who reported that mandatory accreditation shifts the goal to survey compliance instead of quality improvement, does not embed the standards into practice and does not sustain performance. Another reason to reject the requirements may be because of power dynamics, as the results suggest that native Saudis were less motivated to change.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study using interrupted time series analysis showed that the quality performance decreased after the evaluative stage of accreditation 17 . Thus, management mechanisms with a view to assuring the quality and safety of care should be implemented on a permanent basis and assessed in order to strengthen the safety culture in the institution and evidenced in the records to maintain the quality seal of the JCI.…”
Section: Discussionmentioning
confidence: 99%
“…Development of hospital accreditation could increase the public awareness of medical errors and existing gaps in the development of patient safety in the health care system (17). Based on studies have been conducted to evaluate the benefits of accreditation, hospital accreditation can improve the quality and performance of IJHS 2014; 2(2): 61 organizations (18).…”
Section: Introductionmentioning
confidence: 99%